PERAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PASCA PANDEMI COVID-19 - Nada Irfani, Ranu (Institut Daarul Qur'an Jakarta, Indonesia, 2022)
After two years, learning must be carried out online (online) now learning has been carried out normally again. This is a new challenge for teachers and students again, where students and teachers must begin to adapt again to pre-pandemic circumstances. The purpose of this study is to describe and analyze the role of teachers in increasing student learning motivation after the COVID-19 pandemic. This research was conducted at MI Diponegoro 03 Karangklesem. This research is a field research or field research. Data are obtained through observation, interviews, and documentation. In analyzing the data, researchers use reduction, presentation, and verification techniques and drawing conclusions. The results of this study show that the role of teachers in increasing student learning motivation after the Covid-19 pandemic is by means of, creating a fun learning atmosphere, involving student participation, using creative learning media, and utilizing digital media. Student motivation is shown from activeness, participation, enthusiasm, high curiosity, and enthusiasm of students during the excitement of learning in the classroom.